Pulsating aurora from electron scattering by chorus waves - Kasahara, S.; Miyoshi, Y.; Yokota, S.; Mitani, T.; Kasahara, Y.; Matsuda, S.; Kumamoto, A.; Matsuoka, A.; Kazama, Y.; Frey, H. U.; Angelopoulos, V.; Kurita, S.; et al. (Nature (London), 2018)
High-angular-resolution measurements allow the direct observation of the scattering of energetic electrons by chorus waves in the magnetosphere, which causes quasiperiodic electron precipitation that gives rise to pulsating aurorae. Pulsating aurorae A pulsating aurora is a type of aurora that occurs in patches that blink on and off in an almost periodic fashion. They usually arise in the closing phase of an auroral display, at dawn, and cover up to several hundred kilometres of the sky, at an altitude of about 100 kilometres. Many such patches sometimes cover the entire sky. The pulsations arise from intermittent injections of energetic electrons into the upper atmosphere, but just how the injections happen has been unclear because of instrumental limitations on the observations. Satoshi Kasahara and colleagues report observations that show that the energetic electrons are quasiperiodically scattered by 'chorus waves'—intense electromagnetic plasma waves that arise at the magnetic equator and move towards the poles—at the same time as pulsating aurorae are seen from the ground. Auroral substorms, dynamic phenomena that occur in the upper atmosphere at night, are caused by global reconfiguration of the magnetosphere, which releases stored solar wind energy 1 , 2 . These storms are characterized by auroral brightening from dusk to midnight, followed by violent motions of distinct auroral arcs that suddenly break up, and the subsequent emergence of diffuse, pulsating auroral patches at dawn 1 , 3 . Pulsating aurorae, which are quasiperiodic, blinking patches of light tens to hundreds of kilometres across, appear at altitudes of about 100 kilometres in the high-latitude regions of both hemispheres, and multiple patches often cover the entire sky. This auroral pulsation, with periods of several to tens of seconds, is generated by the intermittent precipitation of energetic electrons (several to tens of kiloelectronvolts) arriving from the magnetosphere and colliding with the atoms and molecules of the upper atmosphere 4 , 5 , 6 , 7 . A possible cause of this precipitation is the interaction between magnetospheric electrons and electromagnetic waves called whistler-mode chorus waves 8 , 9 , 10 , 11 . However, no direct observational evidence of this interaction has been obtained so far 12 . Here we report that energetic electrons are scattered by chorus waves, resulting in their precipitation. Our observations were made in March 2017 with a magnetospheric spacecraft equipped with a high-angular-resolution electron sensor and electromagnetic field instruments. The measured 13 , 14 quasiperiodic precipitating electron flux was sufficiently intense to generate a pulsating aurora, which was indeed simultaneously observed by a ground auroral imager.